Initial Stages of Generation and Formation of Public Pre-School Education in Ukraine - Pisots’ka, Leonida (Pedagogical Discourse, 2013)
The article reveals historical approaches to the matter of initiation and formation of public education in Ukraine. On the basis of analysis of historical publications and archival documents the ways of development of pre-school education have been presented. It has been proved that the period starting from the middle of XIX c. to 1917 (XX c.) is the time of initiation of pre-school education and establishment of first public institutions for children. It is characterized by opening public kindergartens for different social strata at the initiative and cost of individuals as well as educational societies. First kindergartens emerged in the 60th of XIX c. upon the initiative of individuals, charity and philanthropic organizations. During that period the foundation for successful activity of state system of public pre-school education was being laid.